2018
DOI: 10.1097/jcp.0000000000000944
|View full text |Cite
|
Sign up to set email alerts
|

Population Pharmacokinetic-Pharmacodynamic Modeling of a Novel Methylphenidate Extended-Release Orally Disintegrating Tablet in Pediatric Patients With Attention-Deficit/Hyperactivity Disorder

Abstract: This model may help facilitate the dose-titration process by identifying an effective MPH XR-ODT target dose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Modeling can also be used with existing long-acting stimulant formulations to inform the dose titration process or make predictions about the relative clinical benefit of formulations that have not been studied in head-to-head trials. Currently, when starting or switching to a new long-acting stimulant, clinicians advise patients to initiate therapy on a low dose and then titrate the dose up until symptom control is achieved without affecting tolerability [141]. However, dose titration can be a time-consuming process that leaves patients at subtherapeutic levels until an optimal dose is determined.…”
Section: Expert Opinionmentioning
confidence: 99%
See 1 more Smart Citation
“…Modeling can also be used with existing long-acting stimulant formulations to inform the dose titration process or make predictions about the relative clinical benefit of formulations that have not been studied in head-to-head trials. Currently, when starting or switching to a new long-acting stimulant, clinicians advise patients to initiate therapy on a low dose and then titrate the dose up until symptom control is achieved without affecting tolerability [141]. However, dose titration can be a time-consuming process that leaves patients at subtherapeutic levels until an optimal dose is determined.…”
Section: Expert Opinionmentioning
confidence: 99%
“…Additionally, when switching from one formulation to another, clinicians are faced with the challenge of determining how to provide comparable coverage quickly without a lapse in response [123]. To date, two separate studies sought to develop the population pharmacokinetic-pharmacodynamic models for MLR-MPH and MPH XR-ODT to simulate pharmacodynamic responses for a range of body weights and doses, with the goal of facilitating the dose titration process by predicting an optimal dose for these formulations based on patient body weight [141,142]. Furthermore, another study sought to develop a pharmacokinetic-pharmacodynamic model for DR/ER-MPH and compare its clinical benefit to four other ER MPH formulations using the previously described model developed by Gomeni and colleagues for formulations with dual release characteristics [143].…”
Section: Expert Opinionmentioning
confidence: 99%
“…For instance, the relationship between systemic methylphenidate concentrations and efficacy in children and adolescents with Attention-Deficit Hyperactivity Disorder was frequently reported, but might be of questionable relevance. Among 160 children and adolescents across three reasonably reported and executed trials, a higher methylphenidate concentration was associated with improved performance, though different instruments were used across the studies [58][59][60]. Most studies judged of lower quality reported similar findings, with one exception [85]; however, the length of the follow-up period was unclear in this work, thus the relationship might have been underestimated.…”
Section: Considering the Relevance Of A Drug Concentration-effect Relmentioning
confidence: 81%
“…Relationships may concern the mother compound, metabolite, or both. side-effects relationship was found for three (venlafaxine [51], desipramine [56], ziprasidone [57]), and a relationship with both efficacy and side-effects for two (methylphenidate [19,[58][59][60], imipramine [61][62][63]). The indications for use of these drugs included major depression, conduct disorder, bipolar disorder, attention-deficit disorder with or without hyperactivity and Tourette syndrome or chronic tic disorder (Table 3).…”
Section: Quality Assessmentmentioning
confidence: 99%
See 1 more Smart Citation